The Effectiveness Of Civil Servant Candidate (PPNS) In Enforcement Of Spatial Planning Laws - Iin Parlina; Siti Rodhiyah Dwi Istinah (Universitas Islam Sultan Agung, 2021)
This study aims to describe the effectiveness of PPNS in enforcing the Spatial Planning Law. In line with the research objectives, in this study using normative juridical research methods, it is concluded: (1) The issuance of Act No. 11 of 2020 concerning Job Creation, has changed the content of Act No. 26 of 2007 concerning Spatial Planning. The legal basis for implementing spatial planning nationally, needs to be synergized in one Government Regulation. PP 21 of 2021 concerning the Implementation of Spatial Planning, integrates various cross-sectoral, cross-regional, and cross-stakeholder interests which are manifested in the preparation of Spatial Plans. Creating conditions for laws and regulations in the field of Spatial Planning that support the investment climate and ease of doing business. Violation of Act No. 11 of 2020, carried out by Civil Servant Investigators (“PPNS”), which are investigators from civil servants to investigate certain criminal acts. The effectiveness of the application of the law for violations of spatial planning, is highly dependent on the legal instruments of each Ministry or government agency/institution. Strengthening legal instruments (both regulations and institutional investigators for PPNS) needs to be taken seriously, because of the lack of legal application for violators of spatial planning. (2) The implementation of spatial planning is still not in accordance with the existing laws and regulations.